Economics of tourism & growth for small island countries. (August 2016) - Stauvermann, Peter Josef; Kumar, Ronald Ravinesh
Abstract: We theoretically analyze the impact of changes in foreign income from tourism source countries on the growth of tourism dependent small island economies. Using a general theoretical construct, we attempt to answer the question of how price elasticity of demand, income elasticity of tourist and the degree of competition in the service sector influence the economic development of small economies. One of the main results is that politicians may consider applying policies which lead to a competitive environment in the service sector to maximize growth and the consequent labor income share. Highlights: A model of tourism and economic growth model is developed. Impact of income change in source countries on destination is examined. Price elasticity of demand, income elasticity of tourist, and degree of competition in service sector are analysed. Modelling presented provides a good framework for applied economic research.